A significant proportion of patients with primary central nervous system lymphoma harbor clonal bone marrow B-cells. Issue 2 (28th January 2019) - Brandt, Anna; Matschke, Jakob; Fehrle, Wilfried; von Wenserski, Lisa; Bokemeyer, Carsten; Illerhaus, Gerald; Binder, Mascha
Abstract: Clonal bone marrow (BM) B-cell populations are a common finding in patients with suspected primary central nervous system lymphoma (PCNSL). To assess their clinical significance, benign monoclonal B-cell lymphocytosis (MBL) needs to be differentiated from concomitant BM involvement, since patients with secondary central nervous system lymphoma (SCNSL) generally require more intensive treatment directed also at the component outside the central nervous system (CNS). Here, we retrospectively analyzed BM samplings in 51 patients with suspected PCNSL. We found clonal B cell populations in 8 of 51 cases (16%) by flow cytometry. None of these eight cases had BM involvement by high-grade lymphoma. No lymphoma relapses outside the CNS were recorded. Together, our data points at a significant percentage of patients with suspected PCNSL harboring clonal BM B-cells, which in this patient group always represented benign MBL. Failure to differentiate these populations from systemic lymphoma involvement may result in overtreatment of patients.